Analysis of Mechanical Properties and Microstructure of Aluminum and Copper Sheet Welding Using Friction Stir Spot Welding Method - Adit Waisal; Hary Munandar; Sofia Debi Puspa; Achdianto; Triyono (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2024)
Welding aluminum and copper materials using friction stir spot welding (FSSW) is widely practiced. Although strong enough, it still produces keyhole and shoulder marks, which are quite large due to the large shoulder and pin sizes. This study investigates the joining of aluminum and copper panels using the FSSW technique using smaller shoulders and pins in different shoulder shapes. The study began by cutting aluminum and copper panels 150 mm long, 50 mm wide, and 5 mm thick. The joining process was carried out at rotational speeds of 900, 1200, and 1500 rpm with tools with several variations in pin length. Pin lengths of 0, 5, and 7 mm with pin diameters made the same at 5 mm, shoulder diameter 20 mm. The connection was observed for macrostructure, microstructure, and hardness. Different tool geometries have the potential to be applied in FSSW joints, especially for sheets. The highest hardness value is found in Cu-Cu material welding, with an average hardness value of 101.63 HVN in the stir zone area. The lowest hardness value is located in the base metal of aluminum material, with an average hardness value of 48.37 HVN.